Diagnostics and correction of static and dynamic disorders of the muskoloskeletal system of wrestlers - Podlivaev, B. A.; Burakov, A. B. (International Journal of Wrestling Science, 2012)
The aim of this research, conducted during preparation of the Russian freestyle wrestling team for the 2012 Olympic games, was to develop methodological approaches for assessing the condition of the musculoskeletal systems of top class athletes, determine the effectiveness of the correction of disorders identified using manual therapy under conditions of continuing intensive physical stress and to develop ways for preventing injuries at all stages of the training process. The diagnostic chart proposed by L.F. Vasilieva was used as a visual method for diagnosing static disorders and the dynamics of the musculoskeletal system for correcting deviations from the functional condition of the musculoskeletal systems of athletes. The chart noted deviations in static (upper part) and movement complexes (lower part) of athletes.